Airflow-induced P(VDF-TrFE) fiber arrays for enhanced piezoelectric energy harvesting - Yong-Il Kim; Dabin Kim; Jihun Jung; Sang-Woo Kim; Miso Kim (APL Materials, 2022)
Piezoelectricity, flexibility, light weight, and biocompatibility of piezoelectric polymer fibers are the desired attributes for energy harvesting and sensing in wearable and biomedical applications. However, the relatively insufficient piezoelectric performance of piezoelectric polymers remains an issue. Here, we demonstrate a considerable increase in P(VDF-TrFE) fiber alignment via electrospinning with a rapidly rotating collector, which substantially enhanced the piezoelectric performance of the fiber mat over a large area. Considering the relationship between the airflow induced near the collector surface and the rotating speed, the collectors with different geometries were systematically compared in terms of the degree of alignment, fiber morphology, and the resulting crystalline electroactive phases of the fibers produced by each collector. We found that the strong airflow induced by the rapid rotation of the modified drum collector contributes to the preferential fiber orientation by pulling and stretching over a large area, which led to an increase in the crystalline electroactive β-phase content responsible for piezoelectricity. As a result, a maximum voltage of 116.6 V and maximum output power of 13.6 µW were achieved using a flexible piezoelectric device comprising a large-area, highly aligned P(VDF-TrFE) fiber mat produced from a modified drum collector at a significantly high speed. This work provides a facile but powerful solution for the wide use of piezoelectric polymer fibers.